Peran Artificial Intelligence dan Blockchain dalam Meningkatkan Cybersecurity pada Proses Akuntansi - Andrayanti, Iin; Rahmadi, Heksawan; Widyasari, Sri Susanti; Ambarwati, Ambarwati (Neraca : Jurnal Akuntansi Terapan, 2024)
Accounting has undergone significant transformation with the adoption of cutting-edge technologies, including Artificial Intelligence (AI), Cybersecurity, and Blockchain. In the contemporary technological landscape, the integration of artificial intelligence (AI), cybersecurity measures, and blockchain technology has emerged as an important development in accounting. The emergence of AI has revolutionised traditional accounting practices by enhancing data processing capabilities and enabling real-time analysis. Through machine learning algorithms, AI can identify patterns and anomalies in financial data, thereby improving accuracy and efficiency while minimising human error. These technological advancements not only streamline operations but also help in predictive analysis, thereby enabling accountants to make informed decisions based on comprehensive data interpretation. In integration with AI, Blockchain guarantees data accuracy and real-time access, allowing auditors to use verified information effectively. The combination of AI and IoT (Internet of Things) and Blockchain accelerates audit procedures, including substantive tests, and enables automated testing of all data, increasing audit efficiency and effectiveness (Kurniawan et al., 2020). In this context, this research will discuss the role and implications of these technologies in improving efficiency, transparency, and security in accounting practices. Organisational culture and industry-specific differences play an important role in shaping technology adoption strategies. The study provides recommendations for corporate firms in Jakarta, emphasising the importance of data security, change management, and skills development. In addition, this study also suggests future research to explore the long-term impact of technology adoption and new technologies in accounting practices. This research contributes to the growing discourse on technology-based transformation in accounting and offers actionable insights for multinational companies operating in a dynamic business environment.